Correction: Huang, Y.-C.; Chen, B.-H. A Comparative Study on Improving Streptozotocin-Induced Type 2 Diabetes in Rats by Hydrosol, Extract and Nanoemulsion Prepared from Cinnamon Leaves. Antioxidants 2023, 12, 29 - Yu-Chi Huang; Bing-Huei Chen (Antioxidants, 2023)
In the original publication [...]